2017
DOI: 10.1111/jvim.14680
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Urine Elimination Behaviors in Cats with a Video Recording System

Abstract: BackgroundUrinary disorders in cats often require subjective caregiver quantification of clinical signs to establish a diagnosis and monitor therapeutic outcomes.ObjectiveTo investigate use of a video recording system (VRS) to better assess and quantify urination behaviors in cats.AnimalsEleven healthy cats and 8 cats with disorders potentially associated with abnormal urination patterns.MethodsProspective study design. Litter box urination behaviors were quantified with a VRS for 14 days and compared to daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
2
10
0
3
Order By: Relevance
“…6 of true UTI. 7 In our study, it was not possible to assess the potential impact of nontreatment of subclinical bacteriuria on either progression of CKD or survival because all cats received antimicrobial treatment, and further work is required to explore this concern. The duration of antimicrobial treatment in our retrospective study also was substantially longer than currently recommended International Society for Companion Animal Infectious Diseases (ISCAID) guidelines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6 of true UTI. 7 In our study, it was not possible to assess the potential impact of nontreatment of subclinical bacteriuria on either progression of CKD or survival because all cats received antimicrobial treatment, and further work is required to explore this concern. The duration of antimicrobial treatment in our retrospective study also was substantially longer than currently recommended International Society for Companion Animal Infectious Diseases (ISCAID) guidelines.…”
Section: Discussionmentioning
confidence: 97%
“…6 However, previous research has found that owners underestimate the frequency of urination in their cats, and the prevalence of true UTI therefore could be underestimated. 7 To date, limited information is available regarding the prognosis of patients with CKD and concurrent UTI or subclinical bacteriuria, either in the human or veterinary medical literature. In people with autosomal dominant polycystic kidney disease (ADPKD), UTI is reported as a risk factor for deteriorating renal function.…”
mentioning
confidence: 99%
“…A doença do trato urinário inferior dos felinos (DTUIF) é um dos problemas mais frequentes na rotina clínica, sendo observado alterações no padrão de micção dos gatos acometidos (Dulaney, Hopfensperger, Malinowski, Hauptman, & Kruger, 2017). O perfil dos animais com DTUIF geralmente inclui gatos machos, castrados, sedentários, obesos, entre 1 a 10 anos de idade, domiciliados, que consomem ração seca e bebem pouca água (Martins et al, 2013).…”
Section: Introductionunclassified
“…A síndrome denominada Doença do Trato Urinário Inferior do Felino (DTUIF), caracterizada por combinação das enfermidades cistite e uretrite, frequentemente culmina na ocorrência de obstrução uretral. A anatomia peculiar da porção peniana da uretra de felinos machos, com uma leve curvatura, favorece a ocorrência de obstruções, seja por urólitos ou por tampões mucosos oriundos de processos inflamatórios (1)(2)(3)(4).…”
Section: Introductionunclassified